Digital Literacy Using Protexan to Detract Herd Stupidity in The Era of Freedom to Learn - Ahmad Muhid; Achmad Bahtiar Efendi (Faculty of Economics, Law, and Humanities, 2022)
There are many problems in implementing the teaching-learning process in the era of freedom to learn. The specific purpose of this research is to provide education on digital literacy learning in English subjects through the Protexan application to detract the herd stupidity in society through students as agents of change in implementing health protocols in the era of freedom to learn. The method used in this research is the research & development (R&D) method. The research was carried out in several stages such as preliminary, prototype creation, expert validation, and media testing. The design and teaching media materials are matched through sorting the data processing at an early stage. This Protexan was tested on educators and students with satisfactory results above 70%. The material is in the form of procedural texts in English following the curriculum in high schools in the independent era of learning. The Covid-19 socialization that is integrated with the learning application is used as additional information for students to continue or to carry out post-pandemic health protocols so that students know what actions need to be taken in the family, friendship, and social spheres to avoid Covid-19.Â